Adapting to climate change by improving water productivity of soils in dry areas - Qadir, Manzoor; Noble, A.D.; Chartres, Colin J. (Wiley, 2013)
Considering extreme events of climate change and declining availability of appropriate quality water and/or highly productive soil resources for agriculture in dryland regions, the need to produce more food, forage and fibre will necessitate the effective utilization of marginal-quality water and soil resources. Recent research and practices have demonstrated that effective utilization of these natural resources in dry areas can improve agricultural productivity per unit area and per unit water applied. This paper focuses on the following three case studies as examples: (1) low productivity soils affected by high levels of magnesium in soil solution and on the cation exchange complex; (2) degraded sandy soils under rainfed conditions characterized by low water-holding capacity, organic matter and clay content and (3) abandoned irrigated soils with elevated levels of salts inhibiting growth of income generating crops. The results of these studies demonstrate that application of calcium-supplying phosphogypsum to high-magnesium soils, addition of clays to light textured degraded soils and phytoremediation of abandoned salt-affected soils significantly improved productivity of these soils. Furthermore, under most circumstances, these interventions were economically viable, revealing that the efficient use of marginal-quality water and soil resources has the potential to improve livelihoods amid growing populations in dry areas while reversing the natural resource degradation trend. However, considerably more investment and policy-level interventions are needed to tackle soil degradation/remediation issues across both irrigated and dryland agricultural environments if the major challenge of producing enough food, forage and fibre is to be met.